STABILITY AND PHENOTYPIC PERFORMANCE OF 16 TEA CLONES (Camellia sinensis var. assamica) ACROSS TWO ENVIRONMENTS DURING THE VEGETATIVE PHASE - Bariza K. Humam; Heri Syahrian; Vitria P. Rahadi; M. Khais Prayoga (Gunung Djati Conference Series, 2026)
Tea (Camellia sinensis var. assamica) is a vital commodity in Indonesia as a raw material for the beverage industry, making early-stage clone screening essential. This study aimed to investigate the stability of growth components and characterize the morphological phenotypic performance of selected tea clones during the vegetative phase. Conducted at the Malabar (West Java) and Semugih (Central Java) plantations from December 2025 to April 2026, the experiment utilized a Randomized Complete Block Design (RCBD) with 16 treatments (15 candidate clones and one check clone, GMB 7) in three replications. Data were analysed using combined ANOVA, Tukey's HSD test (α=5%), and Principal Component Analysis (PCA). Results revealed significant genotype-by-environment (GxE) interactions for plant height and stem diameter at 3 months after planting (MAP), with variations predominantly driven by environmental factors. Clone II.13.2 was significantly shorter than GMB 7 at 3 MAP, while the stem diameters of clones TPS 93/3, TPS 87/2, II.32.15, TPS 87/1, II.6.10, and III.22.15 showed no significant difference compared to the check. Dendrogram analysis placed GMB 7 in a distinct cluster, indicating the candidate clones possess unique vegetative characteristics. Vegetative phase useful for early selection and these potential clones warrant further evaluation for future variety release.